Ankle acute injuries - Khan, K.; Bruker, P. (Encyclopedia of Sports Medicine and Science, 1998)
Description and explanation of: - Functional Anatomy, - Clinical Perspective, - Lateral Ligament Injuries, - Medial Ligament Injuries, - Pott's Fracture, - Persistent Pain: the "Difficult Ankle", - Osteochondral Fractures of the Talar Dome. (Published in: Encyclopedia of Sports Medicine and Science, T.D.Fahey (Editor). Internet Society for Sport Science: http://sportsci.org. 7 March 1998)